Sexual dimorphism in unfused hyoid bones using weight as a parameter - Tyagi, Ashish; Chawla , Hitesh (Journal of Indian Academy of Forensic Medicine, 2019)
The present study aims to determine the sexual dimorphism of unfused hyoid bone by using weight as a parameter. 286 unfused hyoid bones of known sex obtained from the cadavers brought to the mortuary for autopsy were included in the study. 4 measurements were made: weight of the right cornua, weight of the left cornua, weight of the body of the hyoid, and weight of the entire hyoid bone. Measurements were done using an electronic weighing scale and the observations were tabulated. All the measurements in male hyoid bones were greater than the measurementsin female hyoid bones. Univariate discriminant analysis was conducted on the data to estimate sex from the weight of the unfused hyoid bone. The accuracy ranged from 67.5% to 76.6% [62.1% - 73.4% in males and 75.2% - 81.2% in females]. Weights of different parts of unfused hyoid bone showed statistically significant results and can be used to estimate sex along with other parameters.